Diagnostic Reference Levels for Radiology Examination Using General Purpose X Ray Radiography - Hapsari Purbarani, Alviana; Mariyatun; Asih Widiani, Tri; Umaimah, Umi (Rumah Sakit Umum Daerah Dr. Moewardi, 2025)
The local DRL for Dr. Moewardi Hospital is used as a control of patient radiation safety and to measure the quality of radiological examinations conducted at the Radiology Installation of Dr. Moewardi Hospital. The study conducted an assessment on a conventional examination with a General Radiography X-ray plane. The research methodology used was a quantitative approach by using a sample of 30 patients in each examination. X-ray machine data collection was conducted by looking for the Entrance Surface Air Kerma (ESAK) equation, then inputting the patients' data of kV, mAs, FSD, and BSF into the ESAK equation to obtain Entrance Surface Dose (ESD) value of each patient. From ESD data, DRLs were made for each examination using the 3rd quartile data. The results of the study indicated that the local DRL of Dr. Moewardi Hospital was lower than the National DRL of BAPETEN